Right Ventricular Strain Predicts Structural Disease Progression in Patients With Arrhythmogenic Right Ventricular Cardiomyopathy - Malik, Nitin (J Am Heart Assoc, 2020)
BACKGROUND: Arrhythmogenic right ventricular cardiomyopathy (ARVC) is an inherited condition associated with ventricular arrhythmias and myocardial dysfunction; however, limited data exist on identifying patients at highest risk. The purpose of the study was to determine whether measures of right ventricular (RV) dysfunction on echocardiogram including RV strain were predictive of structural disease progression in ARVC. METHODS AND RESULTS: A retrospective analysis of serial echocardiograms from 40 patients fulfilling 2010 task force criteria for ARVC was performed to assess structural progression defined by an increase in proximal RV outflow tract dimensions (parasternal short or long axis) or decrease in RV fractional area change. Echocardiograms were analyzed for RV free‐wall peak longitudinal systolic strain using 2‐dimensional speckle tracking. Risk of structural progression and 5‐year change in RV outflow tract measurements were compared with baseline RV strain. Of the 40 ARVC patients, 61% had structural progression with an increase in the mean parasternal short‐axis RV outflow tract dimension from 36.2 to 38.5 mm (P=0.022) and 68% by increase in parasternal long‐axis RV outflow tract dimension from 36.1 to 39.2 mm (P=0.001). RV fractional area change remained stable over time. Baseline RV strain was significantly associated with the risk of structural progression and 5‐year rate of change. Patients with an RV strain more positive than −20% had a higher risk (odds ratio: 18.4; 95% CI, 2.7–125.8; P=0.003) of structural progression. CONCLUSIONS: RV free wall strain is associated with the rate of structural progression in patients with ARVC. It may be a useful marker in determining which patients require closer follow‐up and treatment.